(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This paper explores the technical challenges of wind energy systems hybridized with solar module systems and suggests possible solutions resulting from the integration of processes in off-grid and grid-connected modes. A general introduction to wind energy is discussed, including how to harvest wind energy, as well as recent advances and developments in wind energy. Particular attention was paid to issues related to wind and photovoltaic (Wind-PV) systems.